Precision medicine with car cells in acute myeloid leukemia: where are we? - Zanetti, Larissa C.; Tomaz, Victoria; de Souza, Ingrid Ferreira; Campregher, Paulo V.; Hamerschlak, Nelson; Kerbauy, Lucila N. (Frontiers in Immunology, 2025)
The integration of chimeric antigen receptor (CAR) therapies with precision medicine holds potential to impact the treatment landscape for acute myeloid leukemia (AML). Genetic mutations play a role in the efficacy of CAR-T and CAR-NK cells, influencing their crucial role in determining the effectiveness of these cells, as well as their proliferation, persistence, resistance, and safety. This review examines how mutations in FLT3, DNMT3A, NPM1, TP53, TET2, gene fusions involving RUNX1 and KMT2A and other key genes modulate CAR-based immunotherapies, highlighting both vulnerabilities and resistance mechanisms. Recent findings demonstrate that mutations in genes such as DNMT3A and NPM1 enhance antigen expression, thereby improving CAR targeting. In contrast, mutations in TP53 drive immune escape and resistance to therapy. Understanding these mutation-specific effects is essential for tailoring CAR therapies to individual patients, optimizing efficacy while minimizing toxicity. By leveraging genomic profiling and personalized engineering approaches, CAR therapies can be refined to overcome resistance and enhance precision in AML treatment. Future research should focus on integrating multiomic data to develop mutation-adapted CAR strategies, ensuring that patients receive the most effective and personalized immunotherapy.